2019
DOI: 10.1002/iub.2131
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐155 inhibition up‐regulates LEPR to inhibit osteoclast activation and bone resorption via activation of AMPK in alendronate‐treated osteoporotic mice

Abstract: Osteoporosis is characterized by a progressive increase in bone fragility, leading to low bone mass and structural deterioration of bone tissue. is highly expressed in osteoporosis. Thus, the current study aimed to investigate the effect of miR-155 on the inhibition of osteoclast activation and bone resorption by targeting leptin receptor (LEPR) through the adenosine monophosphate activated protein kinase (AMPK) pathway in alendronate-treated osteoporotic mice. An osteoporosis mouse model was established to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Moreover, miR-7062-5p also downregulated activation of AMPKα, which can be rescued by overexpression of GPR65; thus, we demonstrated that AMPK is downstream of GPR65, and both of them can be regulated by miR-7062-5p. Numerous evidence demonstrated that activation of AMPK negatively regulated osteoclastogenesis (Dong et al, 2018;Tong et al, 2018;Mao et al, 2019). The AMPK pathway can inhibit the activation of the JNK pathway (Lin et al, 2016;Chen S. et al, 2018, which is a key way of stimulating osteoclast formation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR-7062-5p also downregulated activation of AMPKα, which can be rescued by overexpression of GPR65; thus, we demonstrated that AMPK is downstream of GPR65, and both of them can be regulated by miR-7062-5p. Numerous evidence demonstrated that activation of AMPK negatively regulated osteoclastogenesis (Dong et al, 2018;Tong et al, 2018;Mao et al, 2019). The AMPK pathway can inhibit the activation of the JNK pathway (Lin et al, 2016;Chen S. et al, 2018, which is a key way of stimulating osteoclast formation.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, miR-155 is involved in the regulation of OCs. In osteoporotic mice, miR-155 inhibited OC activation by targeting the leptin receptor ( LEPR) via the AMPK pathway [ 12 ]. MiR-155 can target proto-oncogene SPI1 , microsomia-related transcription factor, and cytokine signal transduction inhibitor protein 1 to inhibit macrophage activation and OC differentiation, thus inhibiting the process of bone resorption [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, miR-155 is involved in the regulation of OCs. In osteoporotic mice, miR-155 inhibited OC activation by targeting the leptin receptor (LEPR) via the AMPK pathway (Mao et al, 2019). MiR-155 can target proto-oncogene SPI1, microsomia-related transcription factor and cytokine signal transduction inhibitor protein 1 to inhibit macrophage activation and OC differentiation, thus inhibiting the process of bone resorption (Song et al, 2019).…”
Section: Discussionmentioning
confidence: 99%